Across-night dynamics in traveling sleep slow waves throughout childhood. Issue 11 (29th August 2018) - Schoch, Sarah F; Riedner, Brady A; Deoni, Sean C; Huber, Reto; LeBourgeois, Monique K; Kurth, Salome
Abstract: Study Objectives: Sleep slow waves behave like traveling waves and are thus a marker for brain connectivity. Across a night of sleep in adults, wave propagation is scaled down, becoming more local. Yet, it is unknown whether slow wave propagation undergoes similar across-night dynamics in childhood—a period of extensive cortical rewiring. Methods: High-density electroencephalography (EEG; 128 channels) was recorded during sleep in three groups of healthy children: 2.0–4.9 years ( n = 11), 5.0–8.9 years ( n = 9) and 9.0–16.9 years ( n = 9). Slow wave propagation speed, distance, and cortical involvement were quantified. To characterize across-night dynamics, the 20% most pronounced (highest amplitude) slow waves were subdivided into five time-based quintiles. Results: We found indications that slow wave propagation distance decreased across a night of sleep. We observed an interesting interaction of across-night slow wave propagation dynamics with age ( p < 0.05). When comparing the first and last quintiles, there was a trend level difference between age groups: 2- to 4.9-year-old children showed an 11.9% across-night decrease in slow wave propagation distance, which was not observed in the older two age groups. Regardless of age, cortical involvement decreased by 10.4%–23.7% across a night of sleep. No across-night changes were observed in slow wave speed. Conclusions: Findings provide evidence that signatures of brain connectivity undergo across-night dynamics specific to maturational periods. These results suggest that across-night dynamics in slow wave propagation distance reflect heightened plasticity in underlying cerebral networks specific to developmental periods.